Requirement of Translation But Not Transcription for the Maintenance of Long-Term Depression in the CA1 Region of Freely Moving Rats - Manahan-Vaughan, Denise (J Neurosci, 2000)
Hippocampal long-term depression (LTD) comprises a persistent reduction in synaptic strength that can be induced in the CA1 region by repeated low-frequency stimulation (LFS). Previous studies have demonstrated that hippocampal long-term potentiation requires de novo protein synthesis. Whether hippocampal LTD is also protein synthesis-dependent is not known. In this study, we investigated if the previous administration of translation inhibitors (anisomycin or emetine) or a transcription inhibitor (actinomycin-D) influenced the profile of LTD in freely moving adult Wistar rats. Seven- to 8-week-old animals underwent chronic implantation of a recording electrode in the CA1 stratum radiatum and a stimulation electrode in the Schaffer collateral/commissural fiber pathway. A cannula was implanted in the ipsilateral cerebral ventricle to enable drug administration. Experiments were commenced 10 d after the implantation procedure. Immediately after application of LFS (1 Hz, 900 pulses) robust LTD was seen that persisted for >8 hr in control animals. Application of anisomycin (240 μg/5 μl) emetine (240 μg/5 μl) before LFS prevented the expression of LTD or ∼4.5 hr after LFS. Previous administration of actinomycin D (72 μg/12 μl) had no effect on the expression of LTD. None of the compounds elicited significant effects on basal synaptic transmission when administered in the absence of LFS. These data suggest that LTD in the CA1 region in vivo is protein synthesis-dependent. Furthermore, persistent LTD can be established through the translation of existing mRNA, whereas de novo mRNA transcription does not appear to be necessary.